2000
DOI: 10.1111/jgs.2000.48.11.1496
|View full text |Cite
|
Sign up to set email alerts
|

The Manchester Respiratory Activities of Daily Living Questionnaire: Development, Reliability, Validity, and Responsiveness to Pulmonary Rehabilitation

Abstract: MRADL is a reliable and valid self-report scale for assessment of physical disability in older COPD patients. It is responsive to pulmonary rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 27 publications
1
36
0
3
Order By: Relevance
“…Strategy of search consisted of the combination of the terms ''COPD and physical activity'' with the terms ''assessment'', ''measurement'', ''quantification'', ''questionnaire'', ''scale'', ''diary'', ''motion sensor'', ''accelerometer'' and ''activity monitor''. Methods aiming to assess functional status [12][13][14][15][16], selfefficacy, performance and independence during ADL [17][18][19][20][21][22][23][24][25][26][27] and the impact of symptoms in usual activities [28][29][30], as well as health-related quality of life questionnaires with subscales of physical activity [31][32][33] and methods to assess functional exercise capacity [34,35], are not discussed in the present review, since they do not aim primarily to quantify the amount and intensity of activity performed in daily life. There were no limitations in terms of study design and sample size, but only articles published in English were included.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategy of search consisted of the combination of the terms ''COPD and physical activity'' with the terms ''assessment'', ''measurement'', ''quantification'', ''questionnaire'', ''scale'', ''diary'', ''motion sensor'', ''accelerometer'' and ''activity monitor''. Methods aiming to assess functional status [12][13][14][15][16], selfefficacy, performance and independence during ADL [17][18][19][20][21][22][23][24][25][26][27] and the impact of symptoms in usual activities [28][29][30], as well as health-related quality of life questionnaires with subscales of physical activity [31][32][33] and methods to assess functional exercise capacity [34,35], are not discussed in the present review, since they do not aim primarily to quantify the amount and intensity of activity performed in daily life. There were no limitations in terms of study design and sample size, but only articles published in English were included.…”
Section: Methodsmentioning
confidence: 99%
“…However, methods used to objectively quantify the amount and intensity of physical activity performed in daily life are not able to detect if physical activity is more easily performed or results in less breathlessness. This is subjective and requires specific instruments (questionnaires, in this case) which aim at investigating symptoms and performance during activities of daily living or exercise [18,19,22,27]. It is therefore suggested that objective methods for assessment of daily physical activities and subjective methods for assessment of functional status or ADL have complementary roles in assessing disability in COPD patients [39].…”
Section: Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The Geriatric Mental State Schedule (GMS) was administered by a blinded research worker (AMY) trained and validated in the use the GMS by a consultant psychiatrist (RCB). Physical disability was measured using the self-complete Manchester Respiratory Activities of Daily Living Questionnaire (MRADL, Yohannes et al, 2000b). Quality of life was assessed by the Breathing Problems Questionnaire (BPQ, Hyland et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, two disease-specific activities of daily living scales, the London Chest Activity of Daily Living (LCADL) [32]and the Manchester Respiratory Activity of Daily Living (MRADL) [33], have been recently reported for use in chronic lung disease. We did not consider the use of these scales for our study purpose.…”
Section: Discussionmentioning
confidence: 99%